2019
DOI: 10.1038/s41598-019-54541-z
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E deficient rats generated via zinc-finger nucleases exhibit pronounced in-stent restenosis

Abstract: The long-term success of coronary stent implantation is limited by in-stent restenosis (ISR). In spite of a broad variety of animal models available, an ideal high-throughput model of ISR has been lacking. Apolipoprotein E (apoE) deficient rats enable the evaluation of human-sized coronary stents while at the same time providing an atherogenic phenotype. Whereas apoE deficient rats have been proposed as animal model of atherosclerosis, to date it is unknown whether they also develop pronounced ISR. We sought t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…All animal experiments were performed after approval (AZ 84-02.04.2012.A277), according to the European legislation and according to the FELASA guideline for the care and use of experimental animals. Eight-week-old apoE +/+ (Sprague Dawley, Charles River, Cologne, Germany) and apoE −/− (SDapoEtm1sage rats; product number: TGRA3710HM9; Compor Zr ® Zinc-finger nuclease target site: 5′ CAGGCCCTGAACCGAttctggGATTACCTGCGCTGGG; NCBI GeneID: NC_005100.2 GenBank; Sigma Aldrich Genetic Engineering Labs, Saint Louis, MO, USA) [ 8 ] rats were fed a normal diet (3.3% crude fat, cholesterol-free) or western type diet (WD, Ssniff Spezialdiaten, Soest, Germany) for 12 weeks. Rats were kept in standardized conditions (21 °C ± 2 °C, 60% ± 5% humidity, and a 12 h light/dark cycle, free access to food and water ad libitum).…”
Section: Methodsmentioning
confidence: 99%
“…All animal experiments were performed after approval (AZ 84-02.04.2012.A277), according to the European legislation and according to the FELASA guideline for the care and use of experimental animals. Eight-week-old apoE +/+ (Sprague Dawley, Charles River, Cologne, Germany) and apoE −/− (SDapoEtm1sage rats; product number: TGRA3710HM9; Compor Zr ® Zinc-finger nuclease target site: 5′ CAGGCCCTGAACCGAttctggGATTACCTGCGCTGGG; NCBI GeneID: NC_005100.2 GenBank; Sigma Aldrich Genetic Engineering Labs, Saint Louis, MO, USA) [ 8 ] rats were fed a normal diet (3.3% crude fat, cholesterol-free) or western type diet (WD, Ssniff Spezialdiaten, Soest, Germany) for 12 weeks. Rats were kept in standardized conditions (21 °C ± 2 °C, 60% ± 5% humidity, and a 12 h light/dark cycle, free access to food and water ad libitum).…”
Section: Methodsmentioning
confidence: 99%
“…In several animal models, species propensity to spontaneously develop atherosclerosis and/or feeding with cholesterol-rich diets have been exploited to induce or accelerate the development of atherosclerotic lesions in experimental settings. Through transgenesis strategies, it is possible to reproduce more efficiently the human disease phenotype in animal models, classically in mice, rats, rabbits, and in the last years in pigs, too ( 136 , 138 , 139 , 141 ). Of note, hypercholesterolemia is almost the unique factor that has been considered in animal-based approaches ( 138 ).…”
Section: Acquired Heart Diseasesmentioning
confidence: 99%
“…Apolipoprotein E (apoE) is a ubiquitous protein, essential for the lipid metabolism in the whole body 1,2 . The role of apoE in lipid metabolism, ensuring the fulfillment of cholesterol homeostasis and adequate clearance to circulating lipids 3,4 is the best known. Numerous studies have shown new other functions of this protein, independent of lipid metabolism, thus highlighting the polymorphism and multifunctionality of apoE 5 .…”
Section: Introductionmentioning
confidence: 99%